Larvicidal Activity of Nerium oleander against Larvae West Nile Vector Mosquito Culex pipiens (Diptera: Culicidae) - Fouad El-Akhal; Raja Guemmouh; Yassine Ez Zoubi; Abdelhakim El Ouali Lalami (Journal of Parasitology Research)
Background. Outbreaks of the West Nile virus infection were reported in Morocco in 1996, 2003, and 2010. Culex pipiens was strongly suspected as the vector responsible for transmission. In the North center of Morocco, this species has developed resistance to synthetic insecticides. There is an urgent need to find alternatives to the insecticides as natural biocides. Objective. In this work, the insecticidal activity of the extract of the local plant Nerium oleander, which has never been tested before in the North center of Morocco, was studied on larval stages 3 and 4 of Culex pipiens. Methods. Biological tests were realized according to a methodology inspired from standard World Health Organization protocol. The mortality values were determined after 24 h of exposure and LC50 and LC90 values were calculated. Results. The extract had toxic effects on the larvae of culicid mosquitoes. The ethanolic extract of Nerium oleander applied against the larvae of Culex pipiens has given the lethal concentrations LC50 and LC90 in the order of 57.57 mg/mL and 166.35 mg/mL, respectively. Conclusion. This investigation indicates that N. oleander could serve as a potential larvicidal, effective natural biocide against mosquito larvae, particularly Culex pipiens.